Smart Farming System for Optimizing Dryland Agriculture in the Indonesia–Timor Leste Border Area - Yovinia Carmeneja Hoar Siki; Yulianti Paula Bria; Donatus J Manehat; Mikel Grimoaldo Kuabib; Wilhelmus Seran (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This community service program aimed to implement an Internet of Things (IoT)-based smart farming system to optimize dryland agriculture in the Indonesia–Timor Leste border area, particularly in Inbate Village, Bikomi Nilulat District, North Central Timor Regency, East Nusa Tenggara Province. Farmers in this region face several challenges, including prolonged dry seasons, limited irrigation facilities, inefficient water management, and fluctuating agricultural productivity. To address these issues, the program introduced a smart farming system consisting of drip irrigation technology, soil moisture sensors, IoT controllers, water pumps, and solar cell energy systems. The implementation methods included field observation, installation of IoT-based irrigation systems, farmer training, mentoring, monitoring, and evaluation activities. The results showed that the smart farming system successfully improved irrigation efficiency, reduced water consumption, and increased crop productivity for onion and vegetable farming. In addition, farmers demonstrated improved understanding and adoption of modern agricultural technologies through practical training and continuous assistance. Evaluation results involving 15 farmers indicated high levels of user satisfaction, irrigation efficiency, and ease of technology use. Overall, the implementation of IoT-based smart farming technology had a positive impact on sustainable dryland agricultural management, farmer capacity building